Literature Review: Risk Factors for Lung Physiological Disorders Due to Exposure to Wood Dust - Prayudha Ardyaswara (Universitas Airlangga, 2021)
Introduction: The wood processing industry in Indonesia is experiencing very rapid development, so there are positive and negative impacts of this industry for the country. The positive impacts that occur such as increased economic growth while the negative impacts that occur include environmental pollution which directly impacts the health of workers. One of the bad effects experienced by workers working in the industrial sector is wood dust. Wood dust is an invisible object that can circulate through the air so that it can enter the body and cause disruption of lung function of workers. The purpose of this research to conduct research on the factors of lung physiology disorders caused by vulnerability to wood dust. Method: The method was used in this research is a literature review by reviewing 10 relevant articles. Results: The effects showed that the method used is the same, which is using cross sectional, and during the study the data collection tools used questionnaires with interviews. In line with the outcomes of the study, factors for pulmonary physiology are not only caused by dust levels that exceeded the threshold value (NAV), but there are several other factors, namely individual characteristics such as length of service, duration of exposure, smoking habits, and use of personal protective equipment (PPE). Moreover, several studies presented bivariate tests to find out the relationship between variables that are factors in the occurrence of pulmonary physiology. Conclusions: Of 10 studies most have performed a bivariate analysis, but just a few have analyzed all the factors causing pulmonary physiology. Keywords: literature review, pulmonary physiology, risk factor, wood dust